Land Magnetic survey along a profile from Akaz to Rutba town and its applications (Baghdad Science Journal, 2012)
A land magnetic survey was carried out along regional profile, which is located at the north part of the Iraqi western desert. It starts from al –Qaam City (at north) toward Rutba City (at south) with a total length of 238km. The survey was carried out along the paved road between the two cities, About 113 measuring points were done with inter-station distance of 2 km (for 198 km) and 2 to 5km (for 40km). Two proton magnetometers were used in this survey. One of them is used for base station monitoring, which was fixed as of Salah Aldin field (Akkas). Its readings were used for diurnal corrections. All magnetic measurements were corrected for normal and topographic corrections. The readings were reduced to a certain base level. The resulted magnetic anomalies show a good correlation with those of Arial - magnetic survey anomalies conducted by (C.G.G, 1974). This is true for those anomalies with wavelength more than 50km. While the land magnetic survey has shown more small anomalies which may reflect near surface sources. In addition, there is a considerable difference between the magnetic intensity values of both surveys. The downward continuation method was used in this study for detecting the depth of magnetic anomaly source. But before applying this method the total magnetic field was converted to its vertical component using computer program packages. The 2.5 mathematical modeling techniques were used for interpreting magnetic anomaly. Several models were suggested according to the geological and geophysical surface and subsurface data. These models clearly suggest that the tectonic of the studied area may be completely affected by deep faults that could reach the basements or even cut it. These faults resulted in tectonic blocks with relative movements that could happen through the geological time, and they may be responsible for the tectonic features of the western desert. These faults could also responsible for the lateral and vertical variations that are noticed in subsurface rocks of the studied area. The subsurface lateral susceptibility variation between the different blocks could result from the variation in physical parameter of the rocks (like porosity, fracture density…) and there is a possibility that rocks beneath 18km (lower crust) still possess some magnetic properties.